Behaviour of Reinforced Concrete Beams with Kenaf and Steel Hybrid Fibre - Sharifah Maszura, Syed Mohsin; Muhd Fareez, Manaf; Noor Nabilah, Sarbini; Khairunisa, Muthusamy (Asian Research Publishing Network (ARPN), 2016)
This paper presents the effect of kenaf fibre and steel fibre mixed and added into reinforced concrete beams. In investigating the structural behaviour of the beams, four-point bending tests were conducted on six beams by considering two distinct parameters; (i) shear reinforcement arrangement (ii) volume of fraction of kenaf fibre and steel fibre. The experimental work consists of six beams, three beams with full shear reinforcement added with fibres by a volume fraction of Vf = 0%, Vf = 1% and Vf = 2%, respectively. Whilst, the other three beams tested with a reduced amount of shear reinforcement added with fibres with a volume fraction of, Vf = 0, Vf = 1% and Vf = 2% were examined. The beam with Vf = 0% kenaf and steel fibre in full shear reinforcement was taken as the control beam. The experimental result suggests promising enhancement of the load carrying capacity (up to 29%) and ductility (up to 22%) as well as controlled crack propagation for the beams with Vf = 1%. Additionally, it was observed that addition of fibres changes the mode of failure of the beam from brittle to a more ductile manner.